#### Answer

$11$

#### Work Step by Step

Using the rule $(a+b)(a-b)=a^{2}-b^{2}$, we obtain:
$(3\sqrt 2-\sqrt 7)(3\sqrt 2+\sqrt 7)$
=$(3\sqrt 2)^{2}-(\sqrt 7)^{2}$
=$(3)^{2}(\sqrt 2)^{2}-(\sqrt 7)^{2}$
=$(9)(2)-(7)$
=$18-7$
=$11$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

$11$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.